Bio-aviation Fuel: A Comprehensive Review and Analysis of the Supply Chain Components - Doliente, Stephen S.; Narayan, Aravind; Tapia, John Frederick D.; Samsatli, Nouri J.; Zhao, Yingru; Samsatli, Sheila (Frontiers in Energy Research, 2020)
The undeniable environmental ramifications of continued dependence on oil-derived jet fuel have spurred international efforts in the aviation sector toward alternative solutions. Due to the limited options for decarbonization, the successful implementation of bio-aviation fuel is crucial in contributing to the roster of greenhouse gas emissions mitigation strategies for the aviation sector. Since fleet replacement with low-carbon technologies may not be a feasible option, due to the long lifetime and significant capital cost of aircraft, “drop-in” alternatives, which can be used in the engines of existing aircraft in a seamless transition, may be required. This paper presents a detailed analysis of the supply chain components of bio-aviation fuel provision: feedstocks, production pathways, storage, and transport. The economic and environmental performance of different potential bio-feedstocks and technologies are investigated and compared in order to make recommendations on short- and long-term strategies that could be employed internationally. Hydroprocessed esters and fatty acids production pathway, utilizing second-generation oil-seed crops and waste oils, could be an effective immediate solution with the potential for substantial greenhouse gas emissions savings. Microalgal oil could potentially offer far greater yields of bio-aviation fuel and reductions in greenhouse gas emissions, but the technology for large-scale algae cultivation is inadequately mature at present. Fischer-Tropsch production pathway using lignocellulosic biomass has the potential for the highest greenhouse gas emissions savings, which could potentially be the solution within the medium- to long-term plans of the aviation industry, but further research and optimization are required prior to its large-scale implementation due to its limited technological maturity and high capital costs. In practice, the “ideal” feedstocks and technologies of the supply chains are heavily dependent on spatial and temporal criteria. Moreover, many of the parameters investigated are interlinked to each other and the measures that are effective in greenhouse gases emissions reduction are largely associated with increased cost. Hence, policies must be streamlined across the supply chain components that could help in the cost-effective and sustainable deployment of bio-aviation fuel.